2012
DOI: 10.1038/icb.2012.34
|View full text |Cite
|
Sign up to set email alerts
|

HspX‐mediated protection against tuberculosis depends on its chaperoning of a mycobacterial molecule

Abstract: New approaches consisting of ‘multistage' vaccines against (TB) are emerging that combine early antigenic proteins with latency-associated antigens. In this study, HspX was tested for its potential to elicit both short- and long-term protective immune responses. HspX is a logical component in vaccine strategies targeting protective immune responses against primary infection, as well as against reactivation of latent infection, because as previously shown, it is produced during latency, and as our studies show,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 43 publications
0
36
0
1
Order By: Relevance
“…Clinical and laboratory strains of Mtb were cultured in Proskauer-Beck (PB) media to prepare the infectivity stocks as previously described [27]. Bacterial stocks were stored in PB media with 20% glycerol at -80°C until used for the mouse infection study.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical and laboratory strains of Mtb were cultured in Proskauer-Beck (PB) media to prepare the infectivity stocks as previously described [27]. Bacterial stocks were stored in PB media with 20% glycerol at -80°C until used for the mouse infection study.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of the gene coding for the 16 kDa antigen is tightly regulated by the DosR transcriptional regulator [24], which would reduce cross-reactivity with antigens from NTM. The 16 kDa has been found to be highly immunogenic and recommended as one of the component antigens in vaccine strategies targeting protective immune responses against primary TB infection, as well as against reactivation of latent infection [25]. This antigen has been used as part of the commercially available TB diagnostic kit, 'pathozyme TB complex plus', together with the 38 kDa antigen [26].…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated that native but not recombinant HSP16 (when administered with the adjuvant dioctadecylammonium bromide) could elicit protection in a mouse model of TB, and in addition, it had the capacity to boost an existing BCG vaccination. Although HSP16 has not previously been linked with an ability to chaperone antigenic material and deliver it to the immune system, this study does suggest that native mycobacterial HSPs could exploit this pathway for other mycobacterial components [15, 109]. …”
Section: Hsps As Infectious Disease Vaccinesmentioning
confidence: 98%
“…Induction of a potentially protective phenotype has also been shown by a DNA vaccine construct that expresses mycobacterial HSP70 fused to the secreted mycobacterial protein MPT51: these studies demonstrated that linkage to the 27 kDa C terminus substrate binding domain of HSP70 was apparently sufficient to induce the protective immune response as no protection was observed using the 44 kDa N-terminal nucleotide binding domain [108]. An investigation into the immunogenicity of native and recombinant mycobacterial HSP16 (HSPx) was recently published [109]. This study indicated that native but not recombinant HSP16 (when administered with the adjuvant dioctadecylammonium bromide) could elicit protection in a mouse model of TB, and in addition, it had the capacity to boost an existing BCG vaccination.…”
Section: Hsps As Infectious Disease Vaccinesmentioning
confidence: 99%